ANALISIS EKONOMI PEDAGANG IKAN SEGAR DI KELURAHAN SEMPAJA TIMUR KOTA SAMARINDA - Gusti Rina Kurniaty; Helminuddin; Diah Dayang Fidhiani (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
The aim of this research were to analyze the Costs, Revenue, Profit or Net Income, Revenue Cost Ratio, Payback Period and the Break Event Point of fresh fish peddlers businesses and fresh fish sellers businesses in Bengkuring Tepian Permai Residence East Sempaja, Samarinda City. The research conducted for seven months since September 2016-March 2017. Sample design was referred by two kind of methodology, for fresh fish peddlers using by Accidental Sampling and for fresh fish sellers using by Purposive Sampling. The results show that the Total Cost that expanded by the fresh fish peddlers averagely is Rp 23,177,892.-/month/peddler and for fresh fish seller is Rp 44,398,931.-/month/seller. Total Revenue for fresh fish peddlers is Rp 28,052,500.-/month/peddler and for fresh fish seller is Rp 55,271,000.-/month/seller. The Profits that gained by the fresh fish peddlers averagely are Rp 4,878,60.-/month/peddler and for fish sellers are Rp 10,872,069.-/month/seller. Revenue Cost Ratio for fresh fish peddlers are 1.21 and for fresh fish sellers are 1.22. Payback Period for fresh fish peddlers averagely is 1.86 month and for fresh fish sellers averagely is 4.68 month. Break Event Point, is: Sale Volume for fresh fish peddlers is 733.04 kg and for fresh fish sellers is 1,251.44 kg. BEP Prices for fresh fish peddlers averagely is Rp. 32,512.-/kg and for fresh fish sellers averagely is Rp 30,102.-/kg. BEP Selling for fresh fish peddlers averagely is Rp 199,791.- and for fresh fish seller averagely is Rp 1,278,680.-.